Praktik Pengelolaan Lahan Pertanian Berdasarkan Kontribusi Makrofauna Tanah di Desa Moutong Kecamatan Tilongkabila Kabupaten Bone Bolango - Fitriah Suryani Jamin (Solusi Bersama : Jurnal Pengabdian dan Kesejahteraan Masyarakat, 2025)
Practical activities as a form of community service have the aim of applying agricultural land management based on the contribution of soil macrofauna in Moutong Village, Tilongkabila District, Bone Bolango Regency, Gorontalo Province. This community service activity involves students using practical methods, namely by directly testing on previously determined land. The importance of managing agricultural land by considering soil macrofauna (such as earthworms, ants, and Zoysia matrella) is an easy and cheap option to maintain the fertility and productivity of agricultural land. The implementation of this activity went smoothly, starting with preparation, implementation, and closing. Participants were enthusiastic and orderly in following the entire series of community service activities. It is hoped that this management will have an impact on the health and sustainability of agricultural land for future generations.